Advertising and promotion an integrated marketing communications perspective - Belch, George E. (George Edward) 1951- (McGraw-Hill Irwin, 2009)
This work continues its advertising focus with an emphasis on IMC. It is the first book to reflect the shift from the conventional methods of advertising to the more widely recognised approach of implementing an IMC strategy.